Resol/montmorillonite nanocomposites obtained by in situ polymerization - Rivero, Guadalupe (2009)
Nanocomposites based on resol resin and layered silicates were obtained by in situ polymerization. An increment in the viscosity and in the content of free formaldehyde in the prepolymer with the addition of clay was observed. It could be attributed to the entrance of small phenol molecules into the galleries modifying the concentration of reagent enabled to react outside the clay galleries. The composites were cured by temperature and it was observed that the type of clay affect their dispersion in the polymer. The unmodified CloisiteVR Nap montmorillonite (CNa) was the best dispersed in the polymeric matrix, whereas the modified montmorillonites (MMTs) showed an interlayer contraction after curing. It seems to be due to the loss of modifiers from the clay or to the different rate of curing inside and outside the galleries. In addition, the composite containing CNa presented higher crosslinking density than the others with modified MMTs. More adhesive strength was observed in that composite as well. It was related with the void content and the polarity of the samples. These results were compared with the ones obtained when the nanocomposites were synthesized by mixing the clay with the prepolymer. The nanocomposites with the addition of CNa showed similar properties independent of the way of synthesis used. However, it seems that the modified clays are better dispersed by mixing with the prepolymer than by in situ polymerization. © 2009 Wiley Periodicals, Inc.